K.A. INOSTRANTSEV’S COLLECTION ON THE TRADITIONAL NOGAI CULTURE STORED IN THE RUSSIAN ETHNOGRAPHIC MUSEUM - Kuzeeva, Zuhra Z.; Zel'nickaa (Slarba), Rica Sotovna (History, Archeology and Ethnography of the Caucasus, 2020)
The article examines a small, but quite rich in its content, collection of items on the traditional Nogai (Karanogai) culture of the Ethnographic Department of the Caucasus, Central Asia and Kazakhstan of the Russian Ethnographic Museum, collected at the beginning of the last century by K.A.Inostrantsev. This collection, stored under the inventory number 333, includes unique materials that have long been lost and have no genuine analogues in the central and regional museums of the country, or in any private collections. The collection contains the interior decoration of the yurt, items of male and female costume, wedding cart (arba), wedding wagon (kibitka) and felt decorations of the wedding wagon of the late 19th – early 20th centuries. The main purpose of the research is to review museum materials, to identify and further study them as an independent scientific source. Works of a completely new nature have been increasingly emerging in the field of the humanities, with an interdisciplinary approach in development, involving digital computer technologies. Studying objects of traditional culture using modern techniques would allow to reveal seemingly sufficiently studied material from a new perspective. In this sense, museum collections play a significant role and, at times, are the only source of traditional material culture and art of some peoples. In this regard, the allocation of the specificity of the information resource of museum material for its further analysis is one of the urgent tasks of present times, both in historical disciplines and in the field of related sciences. In the context of the present study, a detailed analysis of pieces from the collection 333 was carried out, the attribution of items was compiled, and a classification was made.